MILK Symposium review: Microbiological quality and safety of milk from farm to milk collection centers in Rwanda - Ndahetuye, Jean Baptiste; Artursson, Karin; Båge, Renée; Ingabire, Alice; Karege, Callixte; Djangwani, Juvenal; Nyman, Ann-Kristin; Ongol, Martin Patrick; Tukei, Michael; Persson, Ylva (Journal of Dairy Science, 2020)
The aim of this study was to generate knowledge on the most important milk quality and safety attributes, including somatic cell count (SCC), total bacterial count (TBC), Escherichia coli, Salmonella, and Brucella spp. antibodies and antibiotic residues in milk in the chain from farm to milk collection center (MCC) in Rwanda. In addition, we investigated farm and management factors associated with high TBC, SCC, and Salmonella counts. Raw milk was sampled at the farm and MCC levels. Milk samples were taken from dairy farms linked to 2 selected MCC in each of the 4 provinces in Rwanda. In total, 406 bulk milk samples from 406 farms and 32 bulk milk samples from 8 MCC were collected and analyzed. Farm milk average SCC varied between 180 × 103 and 920 × 103 cells/mL, whereas average SCC in milk samples at MCC varied between 170 × 103 and 1,700 × 103 cells/mL. The mean milk TBC of different farms per MCC varied between 1.1 × 106 and 1.6 × 107 cfu/mL, whereas in milk samples from different MCC, the mean TBC ranged between 5.3 × 105 and 2.4 × 108 cfu/mL. The high TBC in milk from MCC suggests proliferation or recontamination of milk by bacteria during transportation. Escherichia coli was detected in 35 of 385 farm milk samples and ranged between 5 cfu/mL and 1.1 × 104 cfu/mL, whereas in milk samples from the MCC, it was detected in 20 out 32 samples varying between 5 cfu/mL and 2.9 × 103 cfu/mL. Overall farm prevalence of Salmonella in milk samples was 14%, but no milk samples from MCC were positive for Salmonella. Five out of 22 bulk milk samples from different MCC were positive for Brucella spp. antibodies, but no Brucella antibodies were detected in milk samples from farms. The prevalence of antibiotic residues as detected by the Delvotest SP NT (DSM, Delft, the Netherlands) was low: 1.3% in farm milk samples and undetected in MCC milk samples. Lack of a separate milking area was associated with high TBC, whereas offering of supplemental feeds, keeping data of past diseases, and an unhygienic milking area were associated with high SCC. Lack of teat washing before milking was the only factor associated with Salmonella contamination of milk at the farm level. This study indicated high TBC and SCC of milk samples at the farm and MCC levels, which indicates both microbial contamination of milk and poor udder health in dairy cows. Presence of E. coli, Salmonella, and Brucella antibodies in milk was common, but finding antibiotic residues in milk was uncommon.
Keywords: Raw milk; Microbial contamination; Dairy chain; Public health; East Africa